How the Quality of Plut Services and Assistance Can Increase MSME Sales in Tulungagung - Henny Rakhmawati; Eni Widhajati; Nurani Nurani; Risma Ananda Nur Maulida (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2024)
This study aims to determine the effect of PLUT service quality and assistance on increasing MSME sales in Tulungagung. This research uses a mix method research type (mixed method) quantitative and qualitative. The test results prove that the results of data analysis 1) Service Quality Variable (X1) has no effect on Sales Increase (Y). Evidenced by the results of the t test which obtained a tcount of 2.649 > ttable of 2.05183 with a significance value smaller than the probability value of 0.015 <0.05 so it can be concluded that service quality has no effect on increasing sales. 2) There is a positive influence on the mentoring variable (X1) on increasing sales (Y). Evidenced by the results of the t test which obtained a tcount value of 1.877 > ttable 1.703 so it can be concluded that Mentoring has an effect on increasing MSME sales in Tulungagung. 3) Quality of Service and Assistance together have no effect on Sales Increase as evidenced by the results of the fcount test 2.146 > ftable 3.35 and a significance value of 0.136.